Improved dielectric properties of CaCu3Ti4O12 films with a CaTiO3 interlayer on Pt/TiO2/SiO2/Si substrates prepared by pulsed laser deposition - Lee, Sung-Yun; Kim, Hui Eun; Jo, William; Kim, Young-Hwan; Yoo, Sang-Im (Electronic materials letters, 2015)
We report the greatly improved dielectric properties of CaCu 3 Ti 4 O 12 (CCTO) films with a 60 nm-thick CaTiO 3 (CTO) interlayer on Pt/TiO 2 /SiO 2 /Si substrates. Both CCTO films and CTO interlayers were prepared by pulsed laser deposition (PLD). With increasing the thickness of CCTO from 200 nm to 1.3 μ m, the dielectric constants ( ε r ) at 10 kHz in both CCTO single-layered and CCTO/CTO double-layered films increased from ∼260 to ∼6000 and from ∼630 to ∼3700, respectively. Compared with CCTO single-layered films, CCTO/CTO double-layered films irrespective of CCTO film thickness exhibited a remarkable decrease in their dielectric losses ( tanδ ) (<0.1 at the frequency region of 1 - 100 kHz) and highly reduced leakage current density at room temperature. The reduced leakage currents in CCTO/CTO double-layered films are attributable to relatively higher trap ionization energies in the Poole-Frenkel conduction model.